Improving Hole Cleaning using Low Density Polyethylene Beads at Different Mud Circulation Rates in Different Hole Angles - Yeu, Wong Jenn; Katende, Allan; Sagala, Farad; Ismail, Issham (Journal of Natural Gas Science and Engineering, 2019)
In oil and gas exploration and development, drilling a hole is one of the first and most expensive operations. The continuous demand from industry to reduce costs and operational problems has resulted in numerous innovative drilling technologies that allow us to drill directionally. Nevertheless, hole cleaning has become a problematic issue in directional drilling because drill cuttings tend to be deposited on the lower side of the deviated hole. Excess accumulation of cuttings significantly reduces the rate of penetration and indirectly increases the operational cost. To improve the cuttings transport efficiency in a deviated hole, low-density polyethylene (LDPE) beads were introduced into water-based mud for hole cleaning. LDPE beads travel rapidly through the mud column due to buoyancy and move the cuttings forward by drag and collision. The interaction between the LDPE beads and cuttings facilitates the cuttings transport process and prevents the cuttings from settling. In this study, different concentrations of LDPE beads (i.e., 1% to 5% by volume) and different flow rates (i.e., 0.4 L/s, 0.6 L/s, and 1.0 L/s) were used to determine the effects on cuttings transport efficiency. In addition, the hole angle was varied from vertical to horizontal to evaluate the significance of LDPE beads in assisting in transporting cuttings. The results denote that more cuttings can be removed from a hole with higher concentrations of LDPE beads in water-based mud. This finding is due to the higher frequency of collisions, which in turn produces larger impulsive force. In addition, the improvement in cuttings transport efficiency enabled by LDPE beads is more significant in a vertical hole than in a highly deviated hole. In summary, LDPE beads are a promising additive for drilling mud to effectively remove drilled cuttings from a hole.
Keywords: Hole cleaning; Cuttings lifting efficiency; LDPE beads; Water-based mud; Hole angles; Flow rate